2012
DOI: 10.1186/1556-276x-7-489
|View full text |Cite
|
Sign up to set email alerts
|

Singly ionized double-donor complex in vertically coupled quantum dots

Abstract: The electronic states of a singly ionized on-axis double-donor complex (D2+) confined in two identical vertically coupled, axially symmetrical quantum dots in a threading magnetic field are calculated. The solutions of the Schrödinger equation are obtained by a variational separation of variables in the adiabatic limit. Numerical results are shown for bonding and antibonding lowest-lying artificial molecule states corresponding to different quantum dot morphologies, dimensions, separation between them, thickne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…2 ) [13,14]. In addition, the effects of exteriors perturbations such as magnetic, electric, and intense laser fields, pressure, and temperature on the electric and optical properties of the particles trapped on QD have been widely investigated in the literature [15][16][17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…2 ) [13,14]. In addition, the effects of exteriors perturbations such as magnetic, electric, and intense laser fields, pressure, and temperature on the electric and optical properties of the particles trapped on QD have been widely investigated in the literature [15][16][17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…They reported that the confinement of the D + 2 system in a QD provides additional possibilities to tune its properties such as the charge distribution of the lowest-lying states, the corresponding energy splittings, and the radiative lifetimes. The energies and eigenfunctions of a singly ionized D + 2 complex in vertically coupled QDs in the presence of a magnetic field were calculated by Manjarres-Garcia et al using a variational separation of variables for different structure morphologies [24]. Recently, Xu and colleagues performed a pump-probe experiment to investigate electron localization in the dissociation of the H + 2 molecule and breaking a chemical bond in real time [25].…”
Section: Introductionmentioning
confidence: 99%